Autist bolalar va ota-ona munosabatlari komponentlarini ilmiy jixatdan tadqiq etilishi (SCIENCE and SOCIETY, 2024)
In this article, the components of the relationship between parents and children with autism syndrome have been analyzed from a scientific point of view. Parents whose child was diagnosed with autism gave recommendations on how to help the child to develop a sense of closeness with the child, to be together in mutual activies, and to increase the child‘s interests aimed at developing